Prototype Rancang Bangun Sistem Cerdas Pengatur Otomasi Suhu, Kelembaban, dan Sirkulasi Udara Pada Greenhouse Menggunakan Metode Fuzzy Logic - Riski Kurniawan; Wijaya Kurniawan; Rizal Maulana (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Population growth from year to year is increased sharply, this has a negative impact on daily food availability. Increasing food needs are inversely proportional to the availability of increasingly narrow land, this must be addressed immediately so that we can avoid a prolonged food crisis. Based on these problems, we need a media that can produce food by using less land, in this case we take the example of a greenhouse. In a previous study, made a mini greenhouse that can regulate the temperature by output adjusting fan speed. In this study, the input parameters used are the DHT11 temperature sensor, keypad, and RTC. Whereas the output of the system is to turn on the power in the form of fans for circulating air and cooling greenhouses and heaters to regulate the heat in the greenhouse. Fuzzy method is applied to the system to control the aquatic in the form of fans and heaters according to needs. There are 2 input variables used in this system, namely temperature with 5 membership functions, and humidity with 3 membership functions. For output, there are 2 variables, namely fan and heater variables, while for rule base it has 15 fuzzy rules. From the test results, the system can work well with the results of fuzzy accuracy reaching 100%. This proves that the system works well in managing automation in the greenhouse.